2006
DOI: 10.5194/acp-6-4321-2006
|View full text |Cite
|
Sign up to set email alerts
|

Emissions of primary aerosol and precursor gases in the years 2000 and 1750 prescribed data-sets for AeroCom

Abstract: Abstract. Inventories for global aerosol and aerosol precursor emissions have been collected (based on published inventories and published simulations), assessed and prepared for the year 2000 (present-day conditions) and for the year 1750 (pre-industrial conditions). These global datasets establish a comprehensive source for emission input to global modeling, when simulating the aerosol impact on climate with state-of-the-art aerosol component modules. As these modules stratify aerosol into dust, sea-salt, su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
1,060
4

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 964 publications
(1,089 citation statements)
references
References 42 publications
25
1,060
4
Order By: Relevance
“…The size and radiative parameters for dust are the same as used by Krinner et al (2006), following Guelle et al (2000) and Balkanski et al (2007). Black carbon is assumed to follow a log-normal size distribution with a median number radius of 11.8 nm, characteristic of freshly emitted soot (Dentener et al, 2006;Jacobson et al, 2004). In the real world, this diameter increases quickly, as BC undergoes ageing and coagulation and can be coated by other aerosols in the atmosphere.…”
Section: Model Descriptionmentioning
confidence: 99%
“…The size and radiative parameters for dust are the same as used by Krinner et al (2006), following Guelle et al (2000) and Balkanski et al (2007). Black carbon is assumed to follow a log-normal size distribution with a median number radius of 11.8 nm, characteristic of freshly emitted soot (Dentener et al, 2006;Jacobson et al, 2004). In the real world, this diameter increases quickly, as BC undergoes ageing and coagulation and can be coated by other aerosols in the atmosphere.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Anthropogenic emissions are obtained from the Reanalysis of the TROpospheric (RETRO) chemical composition inventories (http://retro.enes.org/index.shtml). Biomass burning emissions are obtained from the Global Fire Emissions Database, Version 2 (GFEDv2.1) with 8-day temporal resolution (Randerson et al, 2005) and vertically distributed following the injection heights suggested by Dentener et al (2006) for the Aerosol InterComparison project (AeroCom), because of insufficient information to perform plume rise calculations over West Africa.…”
Section: Model Descriptionmentioning
confidence: 99%
“…For example, in the atmospheric (bulk) sulfur model intercomparison study COSAM (Comparison of large-scale sulfur models; 1999), simulated wet deposition efficiencies for Europe range between 0.1 and 0.5 day −1 , and they are associated with sulfate lifetimes between 6 and 1 days, respectively (Roelofs et al, 2001). A more recent intercomparison study with relatively sophisticated aerosol models, carried out in the framework of the aerosol intercomparison initiative AeroCom, reported a similar behavior with global wet removal efficiencies between 0.15 and 0.3 day −1 for sulfate and global sulfate lifetimes between 3 and 0.5 days (Textor et al, 2006;their Figs. 5d and 4a).…”
Section: Introductionmentioning
confidence: 57%
“…Roelofs: Temperature responses of water vapor and aerosol lifetimes physical and chemical processes, and aerosol removal lead to differences in simulated aerosol burdens and lifetimes. Wet deposition of aerosol, which is subject of this study, is an important removal process for soluble inorganic aerosol species such as sulfate and nitrate, which have a strong anthropogenic signature (Charlson et al, 1992;Dentener et al, 2006). For example, Croft et al (2010) calculate that 53 % and 43 % of global sulfate are removed by stratiform and convective precipitation, respectively, while 4 % is removed by dry deposition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation